The Role of Human Resource Management in Improving Teacher Performance Through Work-Life Balance - Intan Zulfa Atarria Putri; M. Jazilul Lubab A. Masruri; Ni’matus Shofiah; Syunu Trihantoyo; Muhammad Sholeh (Mudir: Jurnal Manajemen Pendidikan, 2025)
Abstract: Human resource management aims to manage and maximize the capabilities of human resources so that they have a significant impact on the organizational goals to be achieved. The aim of this research is how Work-life balance affects teacher performance, what is the role of HR management in supporting Work-life balance for teachers, policies regarding HR management that can improve teachers' Work-life balance and its impact on their performance, the challenges faced by HR management by HR management in creating Work-life balance for teachers. This research method uses a qualitative literature study approach. The data collection technique begins with a literature search originating from national and international articles. The results of this research identify that there is an influence between work life balance and teacher performance, which is characterized by the better the time balance between work and personal life, the teacher performance will increase, the role of HR management in supporting work life balance by creating policies and facilities to balance work and personal life, there are several HR policies that can improve work life balance, namely 1) implementing flexible working hours, providing training and professional development, as well as open communication, in implementing this there are also challenges, namely frequently changing schedules, increasing workloads, frequent time constraints.